Effect of acute exposure to moderate altitude on kinematic variables of the ippon-seoi-nage and its relationship with the countermovement jump in elite judokas - Almeida, F.; Bonitch-Góngora, J.; Padial, P.; De La Fuente, B.; Morales-Artacho, A. J.; Feriche, B. (PLOS ONE, 2018)
This study aimed to assess the effect of acute exposure to moderate altitude on kinematic variables of the ippon-seoi-nage and on the mechanical outputs of the countermovement jump (CMJ). Thirteen elite male judokas from the Spanish Judo Training Centre in Valencia (age: 21.54 ± 2.15 years) participated in the study. All of them performed an incremental CMJ test and an ippon-seoi-nage technique test before (N) and after the ascent to a moderate altitude of 2320 m above the sea level (H). A linear velocity transducer was attached to the bar to assess the mechanical outputs of each loaded CMJ at different percentages of their own body weight (25, 50, 75 and 100%). A wearable sensor was used to assess the kinematic variables (times, accelerations and angular velocities) transferred to a dummy during the technique test. The kinematic variables showed great individual reliability (CV = 8.46% in N; CV = 8.37% in H), which contrasted with low reliability observed when the whole group was considered. The smallest important CV ratio (>1.15) showed that H caused changes in the reliability of the kinematic variables, with some variables becoming more reliable and others losing the reliability they had in N. H also caused small increments in peak velocity across all loads tested in the CMJ (+3.67%; P<0.05). In contrast, no changes in the kinematic variables were verified. In addition, there was no association between leg extension capability and the acceleration (r = -0.16 ± 0.19 in N; r = -0.24 ± 0.19 in H) or angular velocity (r = -0.19 ± 0.24 in N; r = -0.30 ± 0.26 in H) of the ippon-seoi-nage, nor was acute exposure to H found to affect this association (P>0.05). Differences between individual and within-groups CV confirm the individual adaptations that each judoka makes during this technique. Additionally, the CV ratio shows a change in the space-time pattern of the technique in H. Therefore, it would be necessary to include an adaptation period to adapt the technique after the ascent in altitude. Further studies are needed to confirm the relationship and transference from the velocity gains in CMJ during altitude training.